Clinical Impact of Corrective Cast Treatment for Early Onset Scoliosis: Is It a Worthwhile Treatment Option to Suppress Scoliosis Progression Before Surgical Intervention?. Issue 10 (November 2018) - Kawakami, Noriaki; Koumoto, Izumi; Dogaki, Yoshihiro; Saito, Toshiki; Tauchi, Ryoji; Kawakami, Kazuki; Suzuki, Teppei; Uno, Koki
Abstract : Background: Although corrective cast (CC) has been back in use for the treatment of early onset scoliosis (EOS), no studies have reported how clinically meaningful CC was in comparison with brace-only treatment (BT) in EOS. The aim of this study was to investigate the effect of CC treatment in terms of suppression of scoliosis progression before surgery. Methods: This study was designed to conduct a comparison of patients treated at 2 spine institutions differing in treating methods (one: mainly CC with brace, the other: BT). Applying casts were performed without general anesthesia and repeatedly with the interval of 2 to 6 months combined with corrective brace application called alternatively repetitive cast and brace treatment (ARCBT). In total, 58 patients met the following criteria: (1) age at the first visit ⩽6 years, (2) scoliosis ≥40 degrees, (3) conservative treatment≥2 years. Patients with congenital scoliosis were excluded in this study. In total, 58 patients were divided into 2 groups; cast/brace group (C/B-G) and BT group (B-G). Results: There were no significant differences of diagnosis ( P =0.2773), sex ( P =0.0670), age at the first visit ( P =0.1457), scoliosis magnitude ( P =0.1980), and duration for conservative treatment ( P =0.2578) between 2 groups. Most of the patients who were treated with ARCBT, were switched to BT due to lower compliance for CC after the age of around 7 years. The progression of scoliosis during ARCBT and BT were 4.4 and 5.8 degree/y, respectively. Those during ARCBT in C/B-G was 2.8 degree/y comparing with 8.4 degree/y after switch to BT after 7 years of age. There was a significant difference between scoliosis progression during ARCBT in C/B-G and that of B-G ( P =0.0086). Conclusions: This study showed that ARCBT had a significant impact on suppression of scoliosis progression compared with BT in EOS. However, the termination of cast application and the switch to BT may be still a clinical question considering the time to surgical intervention. Level of Evidence: Level III—retrospective comparative study.